Influence of Starch Admixtures and Silver Colloids Stabilised with Starch Hydrolysates on the Course of Electrochemical Potential Difference of Reinforcing Steel in High-chloride Environment - Sybis, Marta; Sybis, Michał; Konował, Emilia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The purpose of the conducted study was to verify whether the use of concrete admixtures with modified starches and starches modified with stabilised silver colloids affects the course of electrochemical potential difference, and hence corrosion, of reinforcing steel in a chloride environment. In the tests, cross-linked starches and products of acid hydrolysis of starch (dextrins) were used as admixtures. The 1-molar aqueous solution of sodium chloride was used as an aggressive environment.
Keywords: concrete; cement paste; dextrins; electrochemical corrosion; nanosilver